Analysis of Financial Technology Regulation, Information Technology Governance and Partnerships in Influencing Financial Inclusion - Prisila Damayanty; Etty Murwaningsari; Sekar Mayangsari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
It aims to show that Indonesia's development of financial inclusion is still low in Southeast Asia, compared with Singapore, Malaysia, and Prisila Damayanty Thailand. Meanwhile, the efforts to increase financial inclusion have not achieved maximum results. There are many problems that occur in fintech business operations, so that the effective financial inclusion can not be realized optimally. This case is based on the literacy and research data sources obtained, such as regulatory aspects, IT governance and partnerships for financial inclusion. The Method is using multiple regression analysis, with a quantitative approach to causality. This type of research uses samples obtained from primary data that are quite safe and varied on registered and licensed Fintech companies in 2021. The results of statistical data processing represent the regulation and partnership cause positive effect significantly on financial inclusion, while information technology governance did not cause a positive effect to financial inclusion. Research is using questionnaire data has the potential to cause respondent subjectivity so that the answers are not relevant to the actual situation. In addition, the research data is also limited. Research contributions can provide information on a number of variables that become obstacles in increasing financial inclusion programs of the government through fintech companies.